Femoral Hernia: Epidemiology and challenges of management in a sub-saharan African Country - Ogbuanya, Aloysius Ugwu-Olisa; Olisa, Fabian Ugonna; Ewah, Richard Lawrence; Nweke, Obinna; Ugwu, Nonyelum Benedett (Asian Journal of Medical Sciences, 2020)
Background: Femoral hernia is peculiar due to its high propensity towards strangulation, high rates of diagnostic pitfalls and occurrence in older patients with multiple comorbidities. Therefore, an updated record of the clinical characteristics and burden of the disease in our locality should be established. Aims and Objectives: This study aimed to document the challenges of diagnosis and outcome of repair of femoral hernia in southeast Nigeria. Materials and Methods: This was a multi-centre retrospective study of adult patients with femoral hernias repaired surgically over twelveyears period. Tests of statistical significances were done. Results: A total of 128 patients were studied and they represented 3.4% and 2.6% of all patients with groin and abdominal wall hernias respectively. There were 116 females and 12 males. The overall rate of missed diagnosis was 14.8%; majority (84.2%) were in the emergency arm. Eighty-one (63.4%) patients presented emergently while 47 (36.7%) were managed electively. In the emergency group, the vast majority (72, 88.9%) presented beyond 24hours from onset of complications. Still on the emergency group, 72 (88.9%) were strangulated, seven (8.6%) were obstructed and 2 (2.5%) were incarcerated at presentation. Overall resection rate was 39.8%, but in the emergency group, it was 63.0%. Prosthetic meshes were used in only 4 (8.5%) of the 47 elective cases. Recurrence rate was Overall morbidity and mortality rates were 43.0% and 10.9% respectively. Late presentation was an independent predictor of mortality (p=0.000). Conclusion: Though femoral hernias are relatively uncommon, the rate of missed diagnosis is high, majority of which occur in the emergency group. Majority presented in emergency and have high propensity towards strangulation with attendant high morbidity and mortality.